Differential response to endothelial epithelial sodium channel inhibition ex vivo correlates with arterial stiffness in humans. Issue 12 (December 2015) - Lenders, Malte; Hofschröer, Verena; Schmitz, Boris; Kasprzak, Bernd; Rohlmann, Astrid; Missler, Markus; Pavenstädt, Hermann; Oberleithner, Hans; Brand, Stefan-Martin; Kusche-Vihrog, Kristina; Brand, Eva
Abstract : Objectives: Recently, the nanomechanical properties (i.e. stiffness) of endothelial cells have been identified as crucial for appropriate endothelial function. One major determinant of endothelial stiffness is the endothelial sodium channel (EnNaC). EnNaC-dependent stiffening leads to reduced nitric oxide release, which is a hallmark for endothelial dysfunction. In the current study, we hypothesized that endothelial function is directly linked to the overall function of the arterial system. Methods: Sixty-four human ex-vivo arterial samples were collected from femoral bypass or vein-stripping procedures. Nanomechanical characteristics of ex-vivo endothelium from isolated arterial side branches were determined using atomic force microscopy. The endothelium's potential to respond to EnNaC inhibition by amiloride was defined as endothelial amiloride index. In addition, patients' arterial stiffness was determined by pulse wave velocity (PWV). Results: Fifty-three percentage of the ex-vivo samples responded 'classically' to amiloride with endothelial softening, whereas 47% of the patients' samples did not. Interestingly, a lack of endothelial softening in the presence of amiloride in vitro was observed with higher frequency among samples obtained from individuals with elevated PWV. Further, an increased PWV was associated with impaired renal function and endothelial dysfunction (higher levels of von Willebrand factor). Conclusions: Here, we report differential responses of human ex-vivo vessels to amiloride. Although the mechanism of differential amiloride response is still unknown, the data indicate that drug action on endothelial function could differ strongly among patients, especially in those with a vascular end-organ damage determined by PWV. Abstract : Supplemental Digital Content is available in the text